2019
DOI: 10.1177/0271678x19852876
|View full text |Cite
|
Sign up to set email alerts
|

Contrast leakage distant from the hematoma in patients with spontaneous ICH: A 7 T MRI study

Abstract: Disruption of the blood–brain barrier (BBB) might play a role in the pathophysiology of cerebral small vessel disease-related ICH. The aim of this study was to assess presence and extent of contrast agent leakage distant from the hematoma as a marker of BBB disruption in patients with spontaneous ICH. We prospectively performed 7 tesla MRI in adult patients with spontaneous ICH and assessed contrast leakage distant from the hematoma on 3D FLAIR images. Thirty-one patients were included (mean age 60 years, 29% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…34 In another study, using FLAIR images of patients with spontaneous intracerebral hemorrhage, the extent of CA leakage distant from the hematoma was shown. 35 However, both studies did not correct for the vascular supply of the CA. A quantitative pharmacokinetic analysis of DCE-MRI requires a, preferably subjectspecific, VIF, which is ideally obtained from a cerebral artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 In another study, using FLAIR images of patients with spontaneous intracerebral hemorrhage, the extent of CA leakage distant from the hematoma was shown. 35 However, both studies did not correct for the vascular supply of the CA. A quantitative pharmacokinetic analysis of DCE-MRI requires a, preferably subjectspecific, VIF, which is ideally obtained from a cerebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, the contrast enhancement of active MS lesions revealed BBB opening with a T 1 ‐weighted DCE‐MRI sequence acquired at multiple, variable time‐points up to 30 min after CA administration 34 . In another study, using FLAIR images of patients with spontaneous intracerebral hemorrhage, the extent of CA leakage distant from the hematoma was shown 35 . However, both studies did not correct for the vascular supply of the CA.…”
Section: Discussionmentioning
confidence: 99%
“…The FETCH study is a multi-center, prospective, cohort study amongst 204 adults that presented with a symptomatic spontaneous ICH confirmed by computed tomography (CT). 9 Patients underwent 3 T and/or 7 T MRI in one of three participating centers (University Medical Centers of Utrecht, Leiden or Nijmegen). Secondary causes were excluded by CT angiography in all and by digital subtraction angiogram if clinically indicated.…”
Section: Study Populationmentioning
confidence: 99%
“…In this consensus, plaque is defined as a focal structure that encroaches into the arterial lumen of at least 0.5 mm or 50% of the surrounding IMT value or demonstrates a thickness > 1.5 mm. 41 People with irregular vessel walls might be more likely to harbor atherosclerotic vessel wall changes and thus might be more prone to develop symptoms, as compared to people with a smoothly thickened vessel wall, despite a similar mean IMT value. 42 In Chapter 2 we demonstrate that spatial inhomogeneity of CCA-IMT might be a measure for a more advanced atherosclerotic disease.…”
Section: Structural Vessel Wall Parametersmentioning
confidence: 97%
“…[38][39][40] IPH may be caused by erythrocyte extravasation from leaky newly formed vessels within the plaque. 41,42 Alternatively, several reports have shown a relation between small fissures in the fibrous cap and IPH, suggestive that IPH can also originate from hemorrhage from the lumen. 25,[43][44][45] IPH results in plaque destabilization because it associated with rapid plaque expansion and can induce a strong inflammatory response due to the degradation of hemoglobin.…”
Section: Atherosclerosis: the Vulnerable Plaquementioning
confidence: 99%